A emergência do campo de música e gênero no Brasil: reflexões iniciais - Durães Zerbinatti, Camila (2018)
Through initial results of the mapping in progress of productions on "women, feminism, gender and music" in Brazil, we present the interpretation that there is an emerging field of shared collective construction in the country. We see the field "music and gender" as a "wave" that emerges in the area of music and has been in the process of construction since 1978. We propose critical reflections related to the field and its relations (internal and external) from the perspective of the feminist musicologies and the feminist epistemologies as well as the relations between theory and practice in the field. Combining quantitative and qualitative approaches, we observe the hybrid, multiple, heterogeneous, collective and plural constitution of the field.